Time to end Rheumatic Heart Disease: Lessons and opportunities from observational registries - Engel, Mark; Ntsekhe, Mpiko; Zühlke, Liesl (SA Heart Journal, 2019)
The fight against Rheumatic Heart Disease (RHD) is at a critical juncture. Despite the adoption of a global resolution by the World Health Assembly against RHD in May 2018, practitioners working in countries where RHD is endemic continue to be faced with an overwhelming clinical burden, lack of surgical and interventional resources, and insufficient opportunities and funding for research. Recent years have seen the publication of several observational registries, most of which were investigator-initiated, not supported by larger research funders, and coordinated by small teams using paper-based infrastructure. This commentary reflects on the lessons and opportunities that these registries have afforded the field and suggests some areas for further investigation.